Spontaneous Remission of Intractable Epilepsy Following Acute Viral Infections - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2004)
Questionnaires regarding the occurrence of seizure remission following infection were sent to pediatric neurologists in 73 university hospitals, children's hospitals, and epilepsy centers in Japan, and the data obtained in 21 cases from 11 institutions were analyzed at St Marianna University School of Medicine, Kawasaki, and other centers.